2021
DOI: 10.1124/jpet.121.000677
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Ameliorates 5-Fluorouracil–Induced Intestinal Mucositis in Mice by Inhibiting JAKs

Abstract: Intestinal mucositis, resulting from 5-fluorouracil (5-FU)-based chemotherapy, subjects patients to great pain and hampers cancer treatment progress. Puerarin, the major active ingredient in Pueraria lobata, exerts anti-inflammatory and anti-oxidative effects. However, whether puerarin has an effect on 5-FU-induced intestinal mucositis remains unknown. We established a mice model of intestinal mucositis through the intraperitoneal injection of 5-FU, and then injected puerarin (50 and 100 mg/kg) intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Recently, it has been documented that the JAK/STAT3 pathway is implicated in the pathogenesis of intestinal mucosal inflammation involving 5-FU-induced IM [28]. In our study, intestinal p-STAT3 expression was markedly activated following a 5-FU injection.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Recently, it has been documented that the JAK/STAT3 pathway is implicated in the pathogenesis of intestinal mucosal inflammation involving 5-FU-induced IM [28]. In our study, intestinal p-STAT3 expression was markedly activated following a 5-FU injection.…”
Section: Discussionsupporting
confidence: 60%
“…In our study, intestinal p-STAT3 expression was markedly activated following a 5-FU injection. Similarly, mice injected with 5-FU exhibited a marked upregulation in p-STAT3 protein expression in colon tissue [28]. Moreover, in 2015, Yuan and his colleagues reported that IL-17 stimulates STAT3 activation, in which Tyr 705 phosphorylation is important for IL-17's mediation of the activation of STAT3 [15].…”
Section: Discussionmentioning
confidence: 98%
“…Puerarin also modulates other chemotherapeutic side effects through non-ion channel mechanisms [118]. For example, 5-fluorauracil (5-FU) associated intestinal mucositis has been shown to be improved through JAK inhibition after puerarin administration [119].…”
Section: Phytochemicals Modulating Cancer Symptomatologymentioning
confidence: 99%
“…Wang et al established a mouse model of intestinal mucositis by intraperitoneal injection of 5-fluorouracil (5-Fu), and then injected puerarin. They found that puerarin could block the production of Janus kinase (JAK), which was originally significantly activated, and thus attenuated the oxidative response in 5-Fu-induced mucositis [ 12 ]. Wu et al used a piglet model infected with porcine epidemic diarrhea virus (PEDV) to give puerarin orally, and found that the activities of total superoxide dismutase, glutathione peroxidase, and catalase in the intestine and plasma of infected piglets increased while the behavior of myeloperoxidase and the concentration of hydrogen peroxide decreased, which alleviated oxidative stress [ 13 ] ( Figure 1 ).…”
Section: Antioxidantmentioning
confidence: 99%